Toponymic Convergence: Place Names and the Root *alb- in Prehistoric Liguria - Perono Cacciafoco, Francesco (2016)
This paper outlines a new epistemological aspect of the so-called Convergence Theory. Its aim is to develop a unified theory which would comprise all the different theories of Indo-European Linguistics. This analysis tries to "reconstruct" a sort of Italian and European "macro-area" (or "micro-area", depending on the point of view), characterized by place names related to the word-root *alb-, with a delineation of the "semantic steps" made over the centuries by this word-root. It seems that Paleo-Ligurian place names of the Alba type, together with Old European river names Albis and their later forms Olb- (> Orb- in Romance Ligurian), do not directly reflect the proto-Indo-European adjective *albho-, 'white'. On the contrary, they all seem to contain a pre-proto-Indo-European extended root *Hal-bh-, 'water', a cognate with the Sumerian ḫalbia (> Akkadian ḫalpium, 'spring', 'well', 'water mass', 'water hole'). Further analysis of the same *Hal-bh- calls for a comparison with the proto-Indo-European root *Hal-, 'nourish'. The proto-Indo-European suffixed form *HwaH-r-, 'water', exhibits a similar diffusion.